Of stars and galaxies: Co-authorship network and research - Xiaoli Hu; Oliver Zhen Li; Sha Pei (China Journal of Accounting Research, 2020)
We examine the association between network centrality and research using the accounting research community setting. We establish co-authorship network using papers published in the five top accounting journals from 1980 to 2016. We find that the co-authorship network in accounting is a "small world" with some most connected authors playing a key role in connecting others. We use machine learning to label published papers with multiple topics and find patterns in topics over time. More importantly, we find that co-authorship network centrality is positively associated with future research productivity and topic innovation and that the impact of centrality on productivity is higher with more senior authors. Further, centrality of an author's co-authors also has an incrementally positive impact. We conclude that network centrality positively influences research output.
Keywords: 650; Network centrality; Co-authorship; Research output; Accounting research community